KAJIAN ETNOBOTANI TANAMAN OBAT TRADISIONAL DI DESA ANCU KECAMATAN KAJUARA KABUPATEN BONEThe diversity of medicinal plants in Indonesia reflects the biological and cultural wealth that has been passed down from generation to generation. This study aims to - Nuraeni; Darojat, Annisa Zakiyah; Hafsah; Nurlaeliana (Jurnal Biogenerasi, 2025)
The diversity of medicinal plants in Indonesia reflects the biological and cultural wealth that has been passed down from generation to generation. This study aims to identify the types of medicinal plants, the parts that are used, how they are obtained, and the methods of processing medicinal plants used in traditional medicine in Ancu Village, Kajuara District, Bone Regency. The research method used was descriptive qualitative with an ethnobotanical approach. Data were collected through observation, interviews, and documentation of 45 respondents consisting of sanro, community leaders, and local residents. The results showed that there were 55 species of medicinal plants from 35 families, with the Myrtaceae and Zingiberaceae families being the most widely used. The most commonly used parts of the plants were leaves (57%), followed by fruit (16%), rhizomes (11%), and stems (7%). The methods of obtaining medicinal plants included cultivation (67%), wild growth (15%), purchase at the market (11%), and collection from gardens (7%). Knowledge about medicinal plants is mostly obtained from traditional healers (83%) and neighbors/relatives (17%). This study is expected to serve as a basis for the preservation of local knowledge and the sustainable development of medicinal plants. Keywords: Ethnobotany, medicinal plants, traditional medicine, sanro, biodiversity.